Analysis of Khawarij Content in the Akidah Akhlak Textbook for Eleventh Grade in Islamic Senior High School - Athiyyaturrahmah, Athiyyaturrahmah (Maharot : Journal of Islamic Education, 2024)
This article aims to find out the content of the Khawarij material contained in the student book akidah akhlak with a scientific approach for the 2013 curriculum specifically designed for the eleventh grade of Madrasah Aliyah. This research is a qualitative study that is of a library research nature. The data collection technique uses the documentation method. The data source for this research is the textbook on the akidah akhlak with a scientific approach for the 2013 curriculum specifically designed for the eleventh grade of Madrasah Aliyah as the primary data source, and several books and research journal articles that are relevant to the discussion as secondary data. The data analysis was conducted using content analysis. The data analysis was conducted using content analysis. The results of this research indicate that the content of Khawarij material in the the student book akidah akhlak with a scientific approach for the 2013 curriculum specifically designed for the eleventh grade of Madrasah Aliyah is suitable for use. Therefore, additional knowledge from the teacher is needed during the learning process so that explanations about the material can be comprehensively understood by the student.